The Influence of Basic Life Support Training on The Knowledge and Skills of Lifeguard Carpulung Resusitation at Sanur Beach - Yusniawati Ni putu; I Wayan Edi Sanjana (Babali Emergency and Disaster Research, 2023)
Introduction: The knowledge and skills of cardiopulmonary resuscitation become important to be known by the lifeguard in the effort to save the drowning victims, so it is expected to save the life of the drowning victim, prevent the victim condition become worse and accelerate the victim's recovery. Then the effort that can be used to improve the knowledge and skills of lung heart pulmonary resuscitation is through basic life support training. The objective is to determine the effect of basic life support training on lung pulmonary cardiac resuscitation skills and skills in Sanur Beach 2018. Methods: This study used pre-experimental research design with one group pretest post-test design approach. Sampling used non-probability sampling with saturated sample technique (total sample). The number of samples this study as many as 17 respondents. Data collection using a knowledge questionnaire and an observation sheet of pulmonary cardiac resuscitation measures. Result: The result of data analysis using non-parametric statistic test that is Wilcoxon Rank Test with significance level 0,05 got p value <0,000 hence Ho rejected Ha accepted which mean there is influence of life support training base to knowledge and skill of heart resuscitation of lung lifeguard at Sanur Beach year 2018. In this study indicates that the more often the basic life support training is the more increasing the knowledge and skills on the lifeguard. Conclusion: Providing good and correct basic living assistance can make the lifeguard help save the drowning victim